2009
DOI: 10.1371/journal.ppat.1000634
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of Human Rotaviruses: Balancing Reassortment with Preferred Genome Constellations

Abstract: Group A human rotaviruses (RVs) are a major cause of severe gastroenteritis in infants and young children. Yet, aside from the genes encoding serotype antigens (VP7; G-type and VP4; P-type), little is known about the genetic make-up of emerging and endemic human RV strains. To gain insight into the diversity and evolution of RVs circulating at a single location over a period of time, we sequenced the eleven-segmented, double-stranded RNA genomes of fifty-one G3P[8] strains collected from 1974 to 1991 at Childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
189
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(206 citation statements)
references
References 41 publications
9
189
1
7
Order By: Relevance
“…Evidence argues against such changes occurring. For example, it has been noted that closely related strains can persist over multiple seasons, and that greater genetic diversity can exist among strains belonging to a single G-type circulating in the same year than strains belonging to that same G-type reemerging 12-15 y later (43,54). It seems unlikely that such strains lose then regain some "fitness factor" during the intervening years.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence argues against such changes occurring. For example, it has been noted that closely related strains can persist over multiple seasons, and that greater genetic diversity can exist among strains belonging to a single G-type circulating in the same year than strains belonging to that same G-type reemerging 12-15 y later (43,54). It seems unlikely that such strains lose then regain some "fitness factor" during the intervening years.…”
Section: Discussionmentioning
confidence: 99%
“…dConsensus sequences from equine complete genome sequences. rotaviruses tend to present constellations of genes that remain stable over time (Heiman et al, 2008;Matthijnssens et al, 2012;McDonald et al, 2009). Human RVA can be divided into three major genome constellations (GI-GIII), being the Wa strain as the prototype for GI, DS-1 for GII and AU-1 for GIII.…”
Section: Discussionmentioning
confidence: 99%
“…Human RVA can be divided into three major genome constellations (GI-GIII), being the Wa strain as the prototype for GI, DS-1 for GII and AU-1 for GIII. This strong association of genes (genome constellations) has been explained by specific interactions of the viral proteins (Benati et al, 2010;Heiman et al, 2008;Iturriza-Gò mara et al, 2003;McDonald et al, 2009). Thus, genes from one specific genome constellation appear to co-segregate, restricting reassortment amongst different genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotavirus has two independent serotypes (G and P types), and they are defined by VP7 and VP4, respectively. Epidemiological studies on rotavirus showed that strains with G-types of G1, G2, G3, and G4 and those with P-types of P[4] and P [8] are the most prevalent causes of rotavirus gastroenteritis in humans (Gentsch et al, 2005;Santos and Hoshino, 2005;McDonald et al, 2009). Furthermore, the rotavirus G/Ptype distribution varies from year-to-year (O'Ryan, 2009).…”
Section: Inhibitory Activity Of Dried Mfrf Against Various Types Of Hrvmentioning
confidence: 99%